2003
DOI: 10.1159/000074514
|View full text |Cite
|
Sign up to set email alerts
|

Serum Insulin-Like Growth Factor-I Levels and Potential Risk of Type 2 Diabetes

Abstract: The effects of circulating insulin-like growth factor (IGF)-I on increasing insulin sensitivity are well recognized. IGF-I may have a further important role in maintaining β-cell mass, and lower IGF-I activity could explain links between small size at birth and risk of type 2 diabetes in short, obese adults. In the representative Avon Longitudinal Study of Pregnancy and Childhood birth cohort, whereas insulin sensitivity is related to early postnatal weight gain, insulin secretion is related to IGF-I level and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 31 publications
(36 reference statements)
1
20
0
1
Order By: Relevance
“…Epidemiologic studies suggest that high levels of IGF-1 are associated with increased risk of breast cancer and higher levels of breast density, but only among pre-menopausal women [29][30][31]33]. There are few studies that have examined IGF-I levels in type II diabetes, but recent prospective epidemiologic studies suggest that higher IGF-I levels may actually lower diabetes risk [48,49]. One study that compared obese diabetics, obese non-diabetics, and lean controls, found that serum IGF-I were elevated among obese women with and without type II diabetes, although only the difference between non-diabetics and controls achieved statistical significance [50].…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiologic studies suggest that high levels of IGF-1 are associated with increased risk of breast cancer and higher levels of breast density, but only among pre-menopausal women [29][30][31]33]. There are few studies that have examined IGF-I levels in type II diabetes, but recent prospective epidemiologic studies suggest that higher IGF-I levels may actually lower diabetes risk [48,49]. One study that compared obese diabetics, obese non-diabetics, and lean controls, found that serum IGF-I were elevated among obese women with and without type II diabetes, although only the difference between non-diabetics and controls achieved statistical significance [50].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, in an adult study population high circulating concentrations of IGF-I were associated with a reduced risk for developing impaired glucose tolerance and type-2 diabetes (34). It has been suggested that IGF-I might have GH-independent effects on insulin sensitivity, and circulating IGF-I levels could have an important role in the regulation of insulin sensitivity and maintenance of insulin secretion (35).…”
Section: Discussionmentioning
confidence: 99%
“…The data from the literature suggest that IGF-1 may have beneficial effect on glucose homeostasis, due to its glucose lowering and insulin sensitizing actions (Kabir et al, 2010). Adult studies suggest that lower IGF-1 level in childhood predict increased risk for developing insulin resistance and type 2 diabetes (Dunger et al, 2003). Moreover, previous studies reported that circulating fasting free IGF-1 were higher in obese subjects compared with normal weight controls, whereas total IGF-1 were not significantly different between the groups (Nam et al, 1997).…”
Section: Discussionmentioning
confidence: 99%